# Chapter 8: Techniques of Integration - Section 8.2 - Integration by Parts - Exercises 8.2 - Page 455: 24

$$\frac{{{e^{2x}}}}{{13}}\left( {3\sin 3x + 2\cos 3x} \right) + C$$

#### Work Step by Step

\eqalign{ & \int {{e^{ - 2x}}\cos 2x} dx \cr & {\text{Using integration by parts method }} \cr & \,\,\,\,\,{\text{Let }}u = {e^{2x}},\,\,\,\,du = 2{e^{2x}}dx,\,\,\,\,\,dv = \cos 3xdx,\,\,\,\,v = \frac{1}{3}\sin 3x \cr & \cr & {\text{Integration by parts then gives}} \cr & \int {{e^{2x}}\cos 3x} dx = \frac{1}{3}{e^{2x}}\sin 3x - \int {\left( {\frac{1}{3}\sin 3x} \right)\left( {2{e^{2x}}} \right)dx} \cr & \int {{e^{2x}}\cos 3x} dx = \frac{1}{3}{e^{2x}}\sin 3x - \frac{2}{3}\int {{e^{2x}}\sin 3xdx} \cr & \cr & {\text{Integration by parts again}} \cr & \,\,\,\,\,{\text{Let }}u = {e^{2x}},\,\,\,\,du = 2{e^{2x}}dx,\,\,\,\,\,dv = \sin 3xdx,\,\,\,\,v = - \frac{1}{3}\cos 3x \cr & \int {{e^{2x}}\cos 3x} dx = \frac{1}{3}{e^{2x}}\sin 3x - \frac{2}{3}\left( { - \frac{1}{3}{e^{2x}}\cos 3x - \int {\left( { - \frac{1}{3}\cos 3x} \right)\left( {2{e^{2x}}dx} \right)} } \right) \cr & \int {{e^{2x}}\cos 3x} dx = \frac{1}{3}{e^{2x}}\sin 3x - \frac{2}{3}\left( { - \frac{1}{3}{e^{2x}}\cos 3x + \frac{2}{3}\int {{e^{2x}}\cos 3xdx} } \right) \cr & \int {{e^{2x}}\cos 3x} dx = \frac{1}{3}{e^{2x}}\sin 3x + \frac{2}{9}{e^{2x}}\cos 3x - \frac{4}{9}\int {{e^{2x}}\cos 3xdx} \cr & {\text{The unknown integral now appears on both sides of the equation}}{\text{. }} \cr & {\text{Adding the integral }}\frac{4}{9}\int {{e^{2x}}\cos 3x} dx{\text{ to both sides and adding }} \cr & {\text{the constant }}C{\text{ we obtain}} \cr & \int {{e^{2x}}\cos 3x} dx + \frac{4}{9}\int {{e^{2x}}\cos 3xdx} = \frac{1}{3}{e^{2x}}\sin 3x + \frac{2}{9}{e^{2x}}\cos 3x + C \cr & \frac{{13}}{9}\int {{e^{2x}}\cos 3x} dx = \frac{1}{3}{e^{2x}}\sin 3x + \frac{2}{9}{e^{2x}}\cos 3x + C \cr & {\text{Divide both sides by }}\frac{9}{{13}} \cr & \int {{e^{2x}}\cos 3x} dx = \frac{9}{{13}}\left( {\frac{1}{3}{e^{2x}}\sin 3x} \right) + \frac{9}{{13}}\left( {\frac{2}{9}{e^{2x}}\cos 3x} \right) + C \cr & \int {{e^{2x}}\cos 3x} dx = \frac{3}{{13}}{e^{2x}}\sin 3x + \frac{2}{{13}}{e^{2x}}\cos 3x + C \cr & \int {{e^{2x}}\cos 3x} dx = \frac{{{e^{2x}}}}{{13}}\left( {3\sin 3x + 2\cos 3x} \right) + C \cr}

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.